The role of corporate governance on financial performance of saccos in Western Uganda. A case study of igara-buhweju tea farmers’ sacco - Precious Ampumuza (Uganda Christian University, 2026)
This study examines the role of corporate governance in influencing the financial performance of SACCOs in Western Uganda with a specific focus on Igara-Buhweju Tea Farmers’ SACCO. The research investigated three key governance dimensions that is; transparency, accountability and board composition. A descriptive cross-sectional design was adopted, and primary data was collected through structured questionnaires from 38 staff members (response rate 64.4%) using a five-point Likert scale. Findings revealed strong and positive perceptions across all three dimensions. Transparency recorded an overall mean of 4.18, with respondents strongly agreeing that information is complete, timely, and rarely falsified. Accountability achieved the second-highest composite mean (4.24), driven particularly by leadership answerability to members (mean 4.63) and accurate reporting during Annual General Meetings. Board composition received the highest overall rating (mean 4.46), with very strong agreement on the consideration of integrity, track record, competence, and stakeholder representation although views on gender balance showed slightly more variation. The results suggest that good transparency, accountability and board composition practices are already contributing to trust, operational efficiency, and financial outcomes at IGABU SACCO. However, minor gaps remain especially in the consistent publication of all public information and achieving fuller gender balance on the board. The study concludes that strengthening these governance elements can further enhance financial sustainability, member confidence, and long-term resilience in SACCOs. It recommends that IGABU improve information accessibility and board diversity initiatives, while Ministry of Trade, Industry and Cooperatives should introduce standardized governance reporting guidelines and regular board training programs for the sector.
Undergraduate